Muhammadiyah dan Program Pemberdayaan Global: Diplomasi Publik Organisasi Islam Lokal - Musfiroh; Listianigrum, Febri (Universitas Pahlawan Tuanku Tambusai, 2025)
As an Islamic organization, Muhammadiyah has played a pivotal role in Indonesia’s public diplomacy through a wide array of empowerment programs at both the national and international levels. Despite its classification as a non-state actor, Muhammadiyah not only advocates moderate Islamic values but also upholds universal principles such as peace, tolerance, and justice. Moreover, it has established educational institutions abroad, provided humanitarian assistance to international communities, engaged in interfaith dialogue, and participated actively in global forums. These efforts have, indirectly yet significantly, bolstered Indonesia’s reputation as a majority-Muslim nation that remains committed to tolerance, diversity, and contributing to world peace. While rooted in Islam, Muhammadiyah advances not solely the interests of the Muslims but embraces broader humanitarian concerns, aligning seamlessly with the goals of Indonesia’s public diplomacy. In doing so, Muhammadiyah has demonstrated that non-state actors can exert a profound influence on a country’s diplomatic outreach.